172k views
5 votes
How do you solve this?

How do you solve this?-example-1
User Micstr
by
6.0k points

1 Answer

2 votes

\bf ~~~~~~~~~~~~\textit{negative exponents}\\\\ a^(-n) \implies \cfrac{1}{a^n} \qquad \qquad \cfrac{1}{a^n}\implies a^(-n) \qquad \qquad a^n\implies \cfrac{1}{a^(-n)} \\\\ -------------------------------


\bf \cfrac{\stackrel{\textit{bacteria's volume}}{1.3* 10^(15)}}{\stackrel{\textit{planet's surface area}}{5.2* 10^(14)}}\implies \cfrac{1.3* 10^(15)* 10^(-14)}{5.2}\implies \cfrac{1.3* 10^(15-14)}{5.2} \\\\\\ \cfrac{1.3* 10}{5.2}\implies \cfrac{13}{5.2}\implies \cfrac{(13)/(1)}{(52)/(10)}\implies \cfrac{13}{1}\cdot \cfrac{10}{52}\implies \cfrac{130}{52} \\\\\\ \cfrac{5}{2}\implies 2(1)/(2)
User Tom Whatmore
by
6.3k points